Efficacy and safety of praziquantel preventive chemotherapy in Schistosoma mansoni infected school children in Southern Ethiopia: A prospective cohort study - Gebreyesus, Tigist Dires; Makonnen, Eyasu; Tadele, Tafesse; Mekete, Kalkidan; Gashaw, Habtamu; Gerba, Heran; Aklillu, Eleni (Frontiers in Pharmacology, 2023)
The World Health Organization recommends efficacy and safety surveillance of anti-helminths used in mass drug administration (MDA) campaigns. We evaluated the effectiveness of single-dose praziquantel against Schistosoma mansoni infection, and the safety of praziquantel plus albendazole preventive chemotherapy (PC) in Schistosoma mansoni infected school children (n=512) in Southern Ethiopia. Stool examinations were done using thick smear Kato-Katz at baseline, week-4, and week-8 of post-MDA to assess praziquantel efficacy. Participants were followed for MDA-associated adverse events up to day 7 of post-MDA. The primary and secondary study outcomes were praziquantel efficacy (parasitological cure and egg reduction rates) and MDA-associated adverse events (AEs), respectively. The overall cure rates at week-4 and week-8 were 89.1% (95%CI=86.1-91.7) and 87.5% (95%CI=83.6 - 90.8), respectively. Cure rates among moderate-to-heavily infected children were significantly lower (p=0.001) compared to those with light infection at week-4 (84.4% vs.91.1%, p=0.03) and week-8 (78.6% vs.91.9%, respectively). Older children had a higher cure rate than younger ones at week-8 (90.1% vs. 79.5%, p=0.01). Among those who were Schistosoma egg-free (cured) at week 4, 7.8% became egg-positive at week 8. The overall egg reduction rate (ERR) at week-4 and week-8 were 93.5% and 91.3%, respectively, being lower among the 5-9 age groups (p=0.01) at week-8. The proportion of children who remained schistosoma egg-positive throughout the study follow-up period was 4.6%, and their ERR at week-4 and week-8 was 50% and 51%, respectively, which is below the 90%WHO threshold for efficacy. The incidence of experiencing at least one type of MDA-associated AEs were 17.0% (95%CI=13.8% - 20.5%); abdominal pain, headache, and vomiting were the most common. The proportion of mild, moderate, and severe AEs was 63.2%, 26.3%, and 10.5%, respectively. Females experienced more AEs than males (p=0.03). Single-dose praziquantel is still effective for the treatment of intestinal schistosomiasis. Praziquantel and albendazole PC is safe and tolerable, and associated AEs are mostly mild-to-moderate and transient. However, the reduced PZQ effectiveness in moderate-to-heavy infection and observed AEs in about one-fifth of infected children underscores the need for better treatment strategies and surveillance for early detection of parasite resistance and management of AEs.